States, Markets and Education The Rise and Limits of the Education State - Weymann, Ansgar; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Education policy is a core element of the state's sovereignty and autonomy. This book analyzes the rise of the western education state and its limits in times of transition from western to non-western globalization and of waning newspaper interest in France, Germany, the UK and the US.
Keywords: Education; Educational policy; ducation and state; Educational sociology; Economic theory; Education and sociology; Sociology, Educational; Political sociology; Education and state; Education; Sociology of Education; Education Policy; Sociology of Education; Political Sociology; Economic Theory/Quantitative Economics/Mathematical Methods; Educational Policy and Politics